Adjacent Segment Infection after Lumbar Fusion: A Case Report and the Literature Review - Wenlong Wang; Zheng Liu; Sijun Wu (Case Reports in Orthopedics)
Introduction. Adjacent segment infective spondylodiscitis is a rare type of surgical spinal infection after lumbar fusion with few reports. We report a further case of adjacent segment infection after three-level lumbar fusion managed successfully with anti-infective therapy and revision surgery. Case Description. A clinical case of a 69-year-old female with multilevel lumbar degenerative disease received three-level fusion. The leading preoperative symptoms were relieved after decompression surgery. However, severe back pain recurred and prompted her to be rehospitalized 2 months later. The signal of spondylitis and discitis at the adjacent segment was detected by magnetic resonance imaging (MRI). No bacteria were identified despite blood cultures being taken before antibiotic treatment. After a long-term anti-infective therapy with vancomycin, the patient gained symptom relief and was discharged home. However, the patient complained of severe back pain again after long-term oral antibiotic treatment and was rehospitalized 6 months after surgery. The computed tomography (CT) scan showed obvious bony endplate destruction at the adjacent segment space. The patient received a debridement operation and autologous iliac bone graft. The infective inflammatory markers were controlled, and the infective space achieved fusion finally. Conclusion. Adjacent segment space infection is a rare reported complication that occurs after spinal fusion surgery. Conservative antibiotic therapy may not control the infection completely, and disc space debridement and autologous iliac bone graft can achieve ultimate fusion and a satisfactory outcome.